Draw2Code: Low-Cost Tangible Programming for Creating AR Animations. - Im, Hyejin.; Rogers, Chris. (Tufts University. Tisch Library., 2023)
Keywords: Augmented Reality, Computational Thinking, K-12 Education, Tangible User Interfaces.; ACM Open.